Crystallographic and spectroscopic studies on palladium(II) complexes containing pyrazole and thiocyanate ligands - Godoy Netto, Adelino V. [UNESP]; Frem, Regina C.G. [UNESP]; Mauro, Antonio E. [UNESP]; Santos, Regina H.A.; Zoia, Jussara R. (Springer Nature, 2002)
Mononuclear palladium(II) complexes containing both pyrazole-type ligands and thiocyanate, of general formula [Pd(SCN) 2(L) 2] {L = pyrazole (HPz) and l-phenyl-3-methylpyrazole (phmPz)} have been prepared and characterized by elemental analysis, i.r. and n.m.r. spectroscopy and by single crystal X-ray diffraction methods. The Pd atom in these structures lies on the crystallographic inversion center; in a square-planar coordination geometry made by two sulfur and two nitrogen atoms of the ligands, both in trans positions.
Keywords: Atoms; Complexation; Crystallography; Infrared spectroscopy; Molecular structure; Nitrogen; Nuclear magnetic resonance spectroscopy; Single crystals; Spectroscopic analysis; Sulfur; X ray diffraction analysis; Palladium complexes; Pyrazole ligand; Thiocyanate ligand; Palladium